SYNTHESIS AND CHARACTERISATION OFCHIRAL MIXEDLIGANDCO(II) COMPLEXES:A STUDY OF BIOLOGICAL SIGNIFICANCE (Indo-American Journal of Life Sciences and Biotechnology, 2025)
Chiral Mixedligand complexes of Cobalt(II), containing two different ligands and one metal center, have been synthesised with the general molecular formula [Co(PClINAP)(aa)·2H₂O], where PClINAP represents the sodium salt of p-chloroisonitrosoacetophenone and "aa" denotes an L-amino acid. Chiral mixed ligand complexes have been characterized using various physicochemical techniques, including elemental analysis, molar conductance measurements, magnetic susceptibility, electronic absorption spectroscopy, infrared (IR) spectroscopy, and thermogravimetric, differential thermal analysis. Based on the obtained data, the bonding and structural features of the complexes have been thoroughly discussed. Additionally, the mixed-ligand metal complexes were evaluated for their biological significance against selected microbial strains.